Identifying potential adopters of aquaponic farming. Issue 2 (29th November 2022) - Greenfeld, Asael; Becker, Nir; Bornman, Janet F.; Angel, Dror L.
Abstract : Integrating fish and plant culture by means of aquaponics has many advantages but is unpopular as a commercial practice. This study identifies barriers to the adoption of aquaponics, and quantitatively predicts potential adoption of aquaponics by Israeli farmers, as a case study. We predict that only a small proportion (4–17%) of potential farmers in Israel would adopt aquaponics within 10 to 12 years from initial exposure. Farmers with the highest predicted rates of adoption were organic growers, followed by fish farmers. Raising profitability would double to triple predicted adoption levels in most grower populations.